Comparative Evaluation of Effects of Propofol and Ketamine versus Dexmedetomidine and Ketamine on Blood Pressure, Heart Rate and Recovery of Patients undergoing Dilatation and Curettage: Effects of Propofol and Ketamine versus Dexmedetomidine and Ketamine in Patients - Farrukh, Raza; Mehreen, Moazma; Qurban, Faiqa; Ather, Salman; Rizwan, Asad; Ovais, Fatima (Pakistan Journal of Health Sciences, 2024)
Cardiovascular stability and fast recovery are fundamentals of anesthesia for day care surgery. Dilatation and curettage is a commonly performed minor surgery in obstetrics and gynecology. Propofol is well-studied agent in short surgical procedures. Dexmedetomidine, popular for conscious and cooperative sedation is being used for minor gynecological procedures nowadays. Objective: To compare the effects of propofol and ketamine combination with dexmedetomidine and ketamine combination on cardiovascular parameters and recovery of patients undergoing dilatation and curettage. Methods: In a quasi-experimental study from March 2021 to August 2021, 136 patients admitted for dilatation and curettage under anesthesia were enrolled. Patients were divided into two groups. Group P+K received intravenous propofol and ketamine and Group D+K received intravenous dexmedetomidine and ketamine. During the procedure, blood pressure, heart rate, oxygen saturation, and recovery time were noted in both groups. Results: The demographic data were comparable in both groups. Group P+K had significantly higher heart rate at 5, 10, 15 min, and at the ending of the procedure as compared to group D+K. Group D+K had significantly higher systolic and diastolic blood pressure at 2 min, 5 min, 10 min, 15 min and at procedure end in comparison with group P+K. Bradycardia was observed in 62 (91.2%) patients in D+K group whereas, in P+K group, hypotension was observed in 16 (23.5%) patients. The mean time to attain MAS (modified aldrete score) of 10 in group P+K was 32.0 ± 2.1 minutes whereas in group D+K was 41.3 ± 2.6 minutes. Conclusions: It was concluded that the use of dexmedetomidine and ketamine in dilatational and curettage provides cardiovascular stability without respiratory depression as compared to propofol and ketamine.